Inferior vena cava (IVC) filters in children: A 10‐year single center experience. Issue 11 (15th July 2015) - Rottenstreich, Amihai; Revel‐Vilk, Shoshana; Bloom, Allan I.; Kalish, Yosef
<x xml:space="preserve">Abstract</x> Background Venous thromboembolism (VTE) is an increasingly recognized problem among children and adolescents. Although inferior vena cava (IVC) filter placement for pulmonary embolism prevention is well reported in adults, data regarding safety and efficacy in the pediatric age group are lacking. Procedure At a large university hospital with a level I trauma center, medical records of children and adolescents who underwent IVC filter insertion were reviewed. Appropriateness of referral for retrieval was assessed in each case. Results Fifty‐nine children and adolescents (mean age 16 years) successfully underwent IVC filter insertion. All filters placed were retrievable. In 47 patients (79.7%), prophylactic filters were placed in the absence of acute VTE in the setting of trauma. In eight patients (13.5%), filters were placed due to contraindication to anticoagulation therapy with concomitant lower extremity deep vein thrombosis or pulmonary embolism. Filters were successfully retrieved in only 12 patients (20.3%), although an attempt at removal was appropriate and feasible in over 90% of cases. Mean duration of follow‐up was 2.1 (range 0.4–7.3) years. A significantly higher retrieval rate was found in patients followed at our thrombosis clinic (P < 0.01). Ten patients (17%) experienced at least one filter‐related complication. Conclusions Although in most cases, IVC filters were placed for prophylactic indications, the evidence to support their role in this setting is limited. Their low retrieval rate and high filter‐related complication rate question their extensive utilization in children. Dedicated follow‐up is necessary to detect complications and to ensure that an attempt at retrieval is made when feasible. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.